1998
DOI: 10.1046/j.1423-0410.1998.7530218.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Stored in a New‐Generation Container

Abstract: During 7 days of storage in a new 1.3-liter platelet container, the pH was maintained above 6.8 in PCs in plasma with a yield between 1.5- and 4.5 x 10(11)/U; when PAS II was used, the maximum platelet yield allowed for comparable pH maintenance was somewhat lower (4.0 x 10(11)/U).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 23 publications
6
39
0
Order By: Relevance
“…Klinger et al [27] used 90% PAS for the preparation of apheresis PCs resulting in an exhausted depletion of glucose after 3 days of storage while buffy coat-derived platelets suspended in 70% PAS revealed acceptable results. In our study, changes in biochemical markers are in line with previous reports examining PAS for buffy coat-derived PCs or for single-donor PCs collected with a different apheresis device [17,20,21,28]. Furthermore, the day-to-day consumption of glucose and the production of lactate are significantly higher if platelets were stored in pure plasma than in T-Sol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Klinger et al [27] used 90% PAS for the preparation of apheresis PCs resulting in an exhausted depletion of glucose after 3 days of storage while buffy coat-derived platelets suspended in 70% PAS revealed acceptable results. In our study, changes in biochemical markers are in line with previous reports examining PAS for buffy coat-derived PCs or for single-donor PCs collected with a different apheresis device [17,20,21,28]. Furthermore, the day-to-day consumption of glucose and the production of lactate are significantly higher if platelets were stored in pure plasma than in T-Sol.…”
Section: Discussionsupporting
confidence: 91%
“…However, the small amount of glucose present from plasma carry-over is sufficient to support platelet metabolism for 5 days [17,18,20]. Further improvement in storage conditions and pH maintenance was obtained by the introduction of new-generation polyolefin containers [21]. So far, most studies have focused on the use of PAS for the preparation and storage of PCs derived from pooled buffy coats.…”
Section: Introductionmentioning
confidence: 99%
“…High correlations were observed between PLT count and pH, pO2, or pCO2, which has been confirmed in the literature. 3,12 Low PLT counts in containers with high gas exchange capacity lead to a diffusion of CO2 out of the container that the formation of CO2 inside the bag exceeds, resulting in a low pCO2 and a high pH. For higher PLT counts, use of O2 and production of CO2 will be more in balance to the diffusion rate.…”
Section: Discussionmentioning
confidence: 99%
“…2 Also it was shown that PCs in plasma in 1.3-L PO remained of good quality for PCs with PLT counts fewer than 450 ¥ 10 9 per PC. 3 In a former study in which PCs prepared from fresh or overnight stored whole blood were compared, it was shown that the PCs from fresh whole blood contained a much lower PLT count compared to PCs from overnight stored whole blood (310 ¥ 10 9 vs. 460 ¥ 10 9 PLTs/PC). 10 Other in vitro variables like pH, pO2, pCO2, glucose and lactate concentration, CD62p expression, and annexin V binding also differed between these preparation techniques and it was hypothesized that this might be caused by the difference in PLT count.…”
mentioning
confidence: 99%
“…Within 20 hours after collecting, the unit of whole blood was separated into its components by high-speed *Address correspondence to this author at the Centro de Transfusión de la Comunidad Valenciana, Avda del Cid 65, 46014 Valencia, Spain; Tel: 34963868143; Fax: 34963502469; E-mail: larrea_lui@gva.es centrifugation in an Heraeus centrifuge (6000, 8000 and 8500) and placed in an automated extractor system (Optipress II, Baxter) for the collection of red blood cells (RBC) and plasma, leaving the BC (volume, 54±2 mL;Hct,52±3%) in the collection bag [2,3]. To obtain PCs following the Council of Europe guidelines [4], 5 iso-group Buffy-coats were pooled diluted with either 300 mL of plasma or 300 mL of PAS-2 (T-Sol, Baxter, Lessines, Belgium) and centrifuge at low speed [5,6]. The resulting ratio of plasma to PAS-2 in the storage medium was approximately 3:7.…”
Section: Pcs Preparationmentioning
confidence: 99%